OTIMIZAÇÃO E VALIDAÇÃO DA EXTRAÇÃO ASSISTIDA POR ULTRASSOM PARA A DETERMINAÇÃO DE IONS METALICOS EM CHIA (Salvia hispanica L.) - Mendivelso, Ericka Johanna Diaz (2016)
The chia (Salvia hispanica L.) provides important nutritional constituents, characterized by high levels of fatty acids and minerals. Despite being recognized as an important source of minerals the studies on the determination of these are still scarce, possibly because of the difficulties in the treatment of the sample, as chia has a high content of organic matter which makes the sample preparation and the determination of metals. Thus, the aim of this study was to optimize and validate the extraction assisted by ultrasound as a sample preparation method for the determination of metal ions in chia seed flour and using the Atomic Absorption Spectrometry in Flame (FAAS). To optimize the extraction assisted by ultrasound was applied to an experimental design 22 in which have been studied the concentration of nitric acid as the extraction solution and the extraction time in the ultrasonic bath. The results of the factorial design allowed set as optimal conditions a 30 minute extraction time and 5% (v / v) nitric acid as the extracting solution for the determination of Mn, Zn, Mg and found that further studies to optimize the Fe and Ca extraction conditions to confirm the reliability of the optimized method validation of the same was carried out by evaluating the linearity parameters, limits of detection (LOD) and quantification (LOQ), precision and accuracy, the application of different statistical methods. The used analytical curves were external standard showed good linearity in the concentration range investigated, with Fregression values> Fcritical and without lack of fit. The limits of detection (LD) and quantitation (LOQ) were below the first point of the calibration curve, indicating that the analyte can be quantified at low concentrations. The accuracy of the method was verified by the variance weighted between two sample preparation methods (digestion by wet and extraction assisted by ultrasound), applying an test F, and the values obtained were lower than Fcritico with p> 0 05, indicating that there are no significant differences in accuracy between the sample preparation methods compared. Precision was also evaluated by the relative standard deviation (RSD (%)) which showed lower values than those recommended by the AOAC in the range of concentrations investigated for Mn and Zn (RDS <5.3%) as well as Mg (RSD < 3.7%). Accuracy was assessed by comparison with a reference method (digestion wet), applying a paired t-test and linear regression analysis for samples of seeds and chia flour. The results obtained for the test-t showed no significant differences in accuracy between the compared methods, since the values found for tcalculated <tcritical with p <0.05 values. In addition, linear regression analysis showed high values of Fregressão confirming that linear models for Mn, Zn and Mg are adequate and the contents of these metal ions show a linear correlation between the sample preparations methods studied. Thus, it can be suggested that this methodology has good accuracy and precision and can be applied in the quality control of flour and chia seeds with advantages over conventional sample preparation methods such as speed, low operating costs and reduced toxic waste.